Effects of dietary fiber on Chinese children with functional constipation and targeted modification of gut microbiota and related metabolites - Xiao, Pei; Song, Ting; Li, Xiao Lu; Xiao, Yong Mei; Wang, Rui Xue; Song, Fei Fei; Li, Dan; Zhang, Ai Hua; Wang, Ying; Zhang, Ting (Frontiers in Nutrition, 2025)
BackgroundAlthough dietary fiber is widely recommended for preventing and treating functional constipation (FC), clinical trial evidence remains limited and the efficacy has not been sufficiently tested in children.PurposeThis study aimed to evaluate the effects of dietary fiber on FC symptoms, while identifying modulations in gut microbiota and associated metabolic changes.ResultsBetween January 1, 2024, and June 1, 2024, a total of 60 patients diagnosed with FC were enrolled in the study across three centers; however, 54 children completed the study. The final cohort consisted of 28 boys and 26 girls, aged 6 to 12 years (mean age: 8.4 ± 1.8 years). Following the dietary fiber intervention, a significant increase in the frequency of complete spontaneous bowel movements (CSBMs) was observed, accompanied by improved stool consistency. Scores for abdominal pain, bloating, and straining showed significant reductions. After 4 weeks of dietary fiber treatment, both richness and diversity of gut microbiota were significantly enhanced. At the genus level, the relative abundances of Lachnospiraceae_ND3007_group, Lactococcus, Prevotella, and Anaerofustis significantly increased, whereas Enterobacter, DTU089, and Sutterella showed significant decreases. Metabolic analysis revealed significant profile alterations. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis identified metabolite-associated pathways, including steroid hormone biosynthesis, alpha-linolenic acid metabolism, and nucleotide metabolism. Pearson correlation analysis established correlations among dietary fiber, gut microbiota, metabolites, and constipation relief. No significant adverse effects were observed.ConclusionIn conclusion, our findings indicate that dietary fiber alleviates constipation and is accompanied by intervention-specific alterations in gut microbiota and metabolites. This research elucidates the interrelationships between constipation, gut microbiota, and metabolites. These insights may enhance our understanding of the pathogenic mechanisms of FC and provide novel therapeutic perspectives.Clinical trials registrationChiCTR2400084125.